Reliable surface area determination of powders and meso/macroporous materials: Small-angle X-ray scattering and gas physisorption - Schlumberger, Carola; Scherdel, Christian; Kriesten, Martin; Leicht, Peter; Keilbach, Andreas; Ehmann, Heike; Kotnik, Petra; Reichenauer, Gudrun; Thommes, Matthias (Microporous and Mesoporous Materials, 2022)
The specific surface area is key for various application fields of porous materials. Its reliable and fast determination is therefore crucial for materials development and product quality management. Surface area assessment is usually based on physical adsorption using the Brunauer-Emmett and Teller (BET) theory. However, the BET method/gas adsorption exhibits a number of limitations and challenges including (i) time consuming sample preparation and measurement time, and (ii) reliable surface areas only possible for non-porous and meso-/macroporous materials to obtain reliable surface areas. In addition, the accuracy of surface area data obtained from adsorption depends on the proper choice of adsorptive/probe. Within this context, this work evaluates in a rigorous way in-depth Small Angle X-ray Scattering (SAXS) as an alternative and complimentary approach for reliable and fast surface area assessment. To our knowledge, this work can be considered the first systematic study where the surface areas from SAXS are compared and validated with true benchmark surface area data. We utilize silica-based nanoparticles as well as a well-defined mesoporous controlled pore glass for systematic SAXS and adsorption studies (argon and nitrogen at 87 K and 77 K, respectively). Owing to the lack of micro- and narrow mesopores of these model materials, the BET method based on argon 87 K adsorption can be applied to determine benchmark surface areas. Indeed, excellent agreement was found between surface areas derived from argon 87 K adsorption and SAXS. In fact, we demonstrate that the determination of specific surface area can be brought with SAXS to a new level, where parameters such as size of the probing adsorptive, its orientation and thus its effective cross-sectional area (when adsorbed on the surface) are no longer affecting the value of the specific surface area determined. Furthermore, SAXS was shown to be significantly faster than gas adsorption. For the silica materials used, the study shows that SAXS does not require degassing and – along with analysis times of only few minutes per sample – provides an accurate and extremely fast, high-throughput approach. This fundamental study can be considered a major step in enabling SAXS for reliable surface area assessment for applications both in nanoporous materials development and quality control, thus boosting SAXS for surface area determination in general, but in particular also for materials, where the usage of gas adsorption is restricted or not possible at all.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Absolute calibration; BET Method; Gas adsorption; Small-angle X-Ray scattering; Specific surface area